2019
DOI: 10.1680/jgeot.17.p.302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increase in load and frequency on the resilience of railway ballast

Abstract: This paper presents the results of a series of large-scale cyclic triaxial tests conducted on ballast subjected to increased load and frequency of loading. For a given loading, the laboratory test data demonstrate that the resilient modulus of ballast is influenced by the frequency of loading. Both strain hardening and strain softening can be observed in response to increasing magnitude of load and frequency. A correlation between the resilient modulus and bulk stress is introduced to describe both the strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 23 publications
(33 reference statements)
4
15
0
Order By: Relevance
“…As expected, the maximum ballast breakage occurs in the 313 top layer, and it decreases in the middle and bottom layers as the induced impact loads attenuate 314 with depth. Figure 11 shows a large increase in ballast breakage when the drop height of the 315 hammer increases (increased impact energy); this agrees with the findings of a previous study 316 using a large-scale triaxial apparatus where ballast breakage was observed to increase with an 317 increase in cyclic loads (Sun et al 2018). 318…”
Section: Measured Lateral Deformation 281supporting
confidence: 82%
See 1 more Smart Citation
“…As expected, the maximum ballast breakage occurs in the 313 top layer, and it decreases in the middle and bottom layers as the induced impact loads attenuate 314 with depth. Figure 11 shows a large increase in ballast breakage when the drop height of the 315 hammer increases (increased impact energy); this agrees with the findings of a previous study 316 using a large-scale triaxial apparatus where ballast breakage was observed to increase with an 317 increase in cyclic loads (Sun et al 2018). 318…”
Section: Measured Lateral Deformation 281supporting
confidence: 82%
“…It is seen that the calculated values of ∆ 3 vary from 10-20 kPa. It 463 is noted that the ASTM D4767-11 recommends the use of a correction factor for rubber membrane 464 stiffness when determining the deviatoric stress in triaxial testing; for ballast assemblies, the 465 required correction for deviator stress is around 10-15 kPa (Lackenby et al 2007, Sun et al 2018. 466…”
Section: Conclusion 401mentioning
confidence: 99%
“…Past studies have been carried out to investigate the effects of the loading characteristics (i.e. monotonic or cyclic loads) on the shear stress-strain responses of railway ballast (Lackenby et al 2007;Sun et al 2018;McDowell and Li 2016, Powrie et al 2007, Biabani et al 2016. Based on an extensive laboratory testing program, the volumetric strains of ballast under monotonic and cyclic loading conditions and at different confining pressures have been evaluated, as shown in Figure 1.…”
Section: Behavior Of Ballast Subjected To Monotonic and Cyclic Loadingsmentioning
confidence: 99%
“…The ballast layer is commonly composed of crushed granular aggregates having a typical thickness of 300mm and is placed underneath the track super-structure and above the capping (subballast) or subgrade. The deterioration (breakage) of ballast is one of the major contributing factors which affect the stability and longevity of railway foundations (Tutumluer et al 2012;Sun et al 2018;Le Pen et al 2011;Ngo et al 2017). The adoption of various forms of geosynthetic inclusions, such as geogrids and rubber energy absorbing drainage sheets (READS) produced from recycled tires to reduce the plastic deformation and breakage of ballast has become increasingly popular worldwide (Navaratnarajah et al 2018;Abadi et al 2019;Indraratna et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The breaking of ballast, including particle crushing/splitting, and severe attrition of aggregates significantly influence the shear strength of ballast (Lackenby et al 2007, Lu and McDowell 2010, Xiao et al 2014a, Ishikawa et al 2011, Sun et al 2018. Indraratna et al (2005) conducted largescale triaxial tests to study the influence of confining pressure (lateral confinement) on the degradation of ballast under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%